A randomized non-inferiority trial of 577nm subthreshold micropulse laser versus half-dose photodynamic therapy for acute central serous chorioretinopathy - Lijun Zhou; Chuangxin Huang; Zijing Li; Tu Lu; Hongkun Zhao; Cong Li; Qifeng Cong; Jiandong Liang; Xiaojing Zhong; Ling Jin; Lin Lu; Chenjin Jin (Photodiagnosis and Photodynamic Therapy)
Purpose: To compare the effectiveness of 577nm subthreshold micropulse laser (SML) with half-dose photodynamic therapy (Hd-PDT) for acute central serous chorioretinopathy (CSC). Method: A non-inferiority clinical trial was performed with a non-inferiority margin of eight letters. Sixty-eight eyes of 68 patients with acute CSC were randomized to the Hd-PDT group or 577 nm SML group. Best-corrected visual acuity (BCVA ), the subretinal fluid (SRF), and the central foveal thickness (CFT) were evaluated at 6 months. Results: The visual acuity significantly improved from 70.38 ± 10.37 at baseline to 83.24 ± 3.03 at 6 months after treatment in the SML group (P < 0.001), from 71.09 ± 10.50 to 84.35 ± 2.09 in the PDT group (P < 0.001). SML was non-inferior to the PDT (mean difference: -0.41, 95% CI: -5.51 – 4.68, P = 0.0021). At the endpoint, CFT was significantly reduced in the two groups, but no statistical difference (P = 0.7694). The complete resolution of SRF reached 82.35% (28/34) in the SML group and 91.18% (31/34) in the PDT group, respectively,but no statistical difference (P = 0.3724). Conclusions: SML was non-inferiority to half-dose PDT in improving the visual acuity for CSC, and it is a viable alternative, especially when the verteporfin in PDT is unavailable.